Analyzing Profitability Ratios to Boost Culinary Menu Performance in Hospitality Business Development - Samuel Hamonangan; Hanif Hasan; Muhammad Halfi Indra Syahputra (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the financial performance of the steak menu at Butcher Steak & Pasta Palembang using three key profitability ratios: Gross Profit Margin (GPM), Return on Sales (ROS), and Return on Capital Employed (ROCE). The method used is descriptive quantitative, with data sourced from sales records and operating costs for the period May to July 2024. This data was strengthened through observation, interviews, documentation, and literature review, thus providing a comprehensive picture of the business's profitability. The results show an average GPM of 43.73%, indicating fairly stable gross profitability. However, this value is still below the industry standard of 75%, mainly due to the high cost of goods sold for key raw materials. This indicates the need for cost control strategies, such as price negotiations with suppliers or innovation in menu engineering to increase gross profit margins. The average ROS was recorded at 43.73%, more than double the industry standard of 20%. This achievement confirms that the restaurant's operations are running efficiently, with effective cost control, resulting in a high net profit from every rupiah of sales. Furthermore, the ROCE ratio averaged 127.57%, significantly exceeding the industry benchmark of 40%. This indicates that the capital used in restaurant operations has been utilized very efficiently and has generated significant returns. Month-to-month performance fluctuations were relatively small, with a slight decline in June and a rebound in July. Overall, this study reveals that while operational efficiency and capital utilization have been excellent, there is still room for improvement in gross profitability. These findings not only provide practical recommendations for restaurant management but also enrich the literature on profitability analysis in the hospitality and culinary sectors.